Need for the development of competencies in palliative care during the undergraduate of the medical career: Necesidad del desarrollo de competencias en cuidados paliativos durante el pregrado de la carrera de medicina - Sánchez-Ruiz, Rubén R. (2022)
Dear editor,Palliative Care (PC) aims to improve the quality of life and alleviate the suffering of patients with serious and incurable conditions. With the aging of the population and the higher prevalence of chronic diseases, the number of people in need of this care has increased. PC is multidimensional and interdisciplinary; and can be provided at different levels of care by both general practitioners and specialists. Therefore, adequate training in this discipline must be required during the medicine degree to allow the development of the necessary skills for its application in medical practice.